Biomarkers of Acute Lung Lesion - Ye. V. Grigoryev; Yu. A. Churlyaev; A. S. Razumov (Общая реаниматология)
The paper analyzes the data available in the literature on the diagnostic value of biological markers of acute lung lesion (ALL) in critical conditions. The study of the diagnostic and prognostic values of biological markers of ALL is shown to be a promising line in the section of critical conditions. The biological markers of ALL will have the highest effectiveness in evaluating the development of ALL at the preclinical stage, in differentiating the exudative and proliferative stages of ALL/acute respiratory distress syndrome, and defining indications for respiratory support. The biological markers of ALL are capable to predict the development of ventilator-induced lung lesion. The analysis of gene expression and the study of an array of DNA nucleotide sequence in the cells are of the greatest diagnostic and prognostic value in determining the predisposition of cytokines and intercellular signal molecules to synthesis.